Virtual Reality's Impacts on Learning Results in 5.0 Education : a Meta-Analysis - Faiqotuzzulfa, Faiqotuzzulfa; Putra , Samudra Arif (Pandawan Sejahtera Indonesia, 2022)
In recent years, the use of virtual reality (VR) in the classroom has grown in popularity. New learning possibilities are made possible by its presence and immersive design. Due to this expansion, several research have been done to determine how VR affects learning results. Meta-analyses that condense the impacts of VR on learning acquisition are now necessary due to the growth of experimental investigations. However, there are a number of evaluations in the present literature that concentrate on 5.0 students and examine the impact of a number of factors, including immersion level, length of intervention, and subject matter. However, there are a number of evaluations in the present literature that concentrate on 5.0 students and examine the impact of a number of factors, including immersion level, length of intervention, and subject matter. To fulfill this demand, this meta-analysis was conducted. Eight experimental papers were eventually included in the meta-analysis following a pre-selection of 286 references published between 2010 and 2021this . The findings demonstrate that, generally speaking, VR fosters greater student learning than the control conditionApart from that, the effect is considerably more pronounced with immersive VR than with semi-immersive and nonimmersive systems. This effect is independent of the level of education in which VR is used and most areas of knowledge. Additionally, shorter treatments are less successful than longer ones.